Customer Relation Management (CRM) system for Customer Service Management - Lian, Shunding (2023)

(untitled)
This is a development-based project for a Customer Relationship Management (CRM) system for Customer Service Management. A CRM system is mainly used in businesses from small to large scale. A CRM system is a part of a module within the Enterprise Resources Planning (ERP) system, whereby it covers multiple functionalities from streamlining a company’s organizational processes to automating them. A CRM system, however, is focused on improving the relationship between a company and its customers through the usage of various types of tools within the system such as sales process streamlining, product recommendation analysis and customer service ticket management. In the real world within the business field, competition is inevitable, and a high customer churn rate is something hard to attain yet important for the growth and sustainability of a company. Customers are the source of success for a business since a business with a high customer churn rate affects the development of the company such that it may lead to the fall of the company if the customer base of the company cannot be secured. Besides, many existing CRM products are heavily focused on the pre-sales closing processes, while neglecting the after-sales process. Thus, this project aims to develop a CRM system, that focuses on customer service management. This project aims to cover some problems within existing systems, which will be covered in Chapter 2 of this paper. The system will employ some basic functionalities within a CRM system such as user profiling that includes full-fledged CRUD operations, a chat bot functionality, ticket management system, and finally a user dashboard that centralizes the ticketing management process where analytics will be shown. Some tools and frameworks that will be employed in this project include ASP.Net Core, Blazor Server App, Entity Framework Core, Dapper, C#, SQL Server RDBMS, Azure Cognitive Services, Syncfusion Components and so on.